Climatic variability, plasticity, and dispersal: A case study from Lake Tana, Ethiopia. Issue 87 (October 2015) - Grove, Matt; Lamb, Henry; Roberts, Helen; Davies, Sarah; Marshall, Mike; Bates, Richard; Huws, Dei
Abstract: The numerous dispersal events that have occurred during the prehistory of hominin lineages are the subject of longstanding and increasingly active debate in evolutionary anthropology. As well as research into the dating and geographic extent of such dispersals, there is an increasing focus on the factors that may have been responsible for dispersal. The growing body of detailed regional palaeoclimatic data is invaluable in demonstrating the often close relationship between changes in prehistoric environments and the movements of hominin populations. The scenarios constructed from such data are often overly simplistic, however, concentrating on the dynamics of cyclical contraction and expansion during severe and ameliorated conditions respectively. This contribution proposes a two-stage hypothesis of hominin dispersal in which populations (1) accumulate high levels of climatic tolerance during highly variable climatic phases, and (2) express such heightened tolerance via dispersal in subsequent low-variability phases. Likely dispersal phases are thus proposed to occur during stable climatic phases that immediately follow phases of high climatic variability. Employing high resolution palaeoclimatic data from Lake Tana, Ethiopia, the hypothesis is examined in relation to the early dispersal of Homo sapiens out of East Africa and into the Levant. A dispersal phase is identified in the Lake Tana record between c. 112, 550 and c. 96, 975 years ago, a date bracket that accords well with the dating evidence for H. sapiens occupation at the sites of Qafzeh and Skhul. Results are discussed in relation to the complex pattern of H. sapiens dispersal out of East Africa, with particular attention paid to the implications of recent genetic chronologies for the origin of non-African modern humans.